Sinergi Kolaboratif Lintas Sektor melalui Program PADU: Strategi Mewujudkan Pembangunan Kota Bitung yang Inklusif dan Berkemajuan - Rahman, Asep; Ramadhani, Shafira Zulfa; Renata, Donna Christha; Asaloei, Sandra Ingried; Makaminang, Mega Yanti; Kusnaedi, Clarissa Evania (Yayasan Bina Lentera Insan, 2026)
People with disabilities in Bitung City still face significant challenges in accessing formal education, skills training, and economic opportunities, which consequently limits their social participation. This study aims to explore development strategies for the Pusat Ajar Disabilitas Unggul (PADU) Program, a collaborative initiative between PT Pertamina Patra Niaga Integrated Terminal Bitung, Yayasan Bina Lentera Insan, and Komunitas Tuli Peduli Bitung aimed at establishing an inclusive ecosystem. The research employs a mixed-methods approach, combining descriptive quantitative analysis by examining participants' pre-test and post-test results with qualitative methods via Focus Group Discussions (FGD) involving 25 informants from the government, private sector, and community organizations. The results indicate that while the PADU Program is effective in enhancing participants' technical skills (such as sewing, barista skills, and crafts), its sustainability is still hindered by weak cross-sector synchronization, instructors' limited proficiency in sign language communication, and post-training market access barriers. This study recommends a programmatic transformation through three main pillars: ecosystem integration with formal institutions (the Disability Services Unit/ULD and the Vocational Training Center/BLK), human resource competency standardization through certification, and the formalization of strategic partnerships via Memorandums of Understanding (MoU) to ensure budgetary sustainability and broader market access.